Discoxenus Wasmann new to China with description of a new species (Coleoptera: Staphylinidae: Aleocharinae) - Xu, Wang; Cai, Yu-Jie; Zeng, Qing-Huai; Wang, Wei-Min; Yu, Xin-Fan; Song, Xiao-Bin (Zootaxa, 2022)
The termitophilous genus Discoxenus Wasmann, 1904 (Aleocharini: Compactopediina) is recorded from China for the first time and a new species from Guangdong is described under the name: Discoxenus shenzhenensis sp. nov.